2019
DOI: 10.1021/acs.langmuir.9b01064
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Contact Angle Tuning of Silver Nanostructures by Laser Heating in Different Fluid Ambient

Abstract: It has been theoretically suggested by Yan et al. (Colloids Surf., A 2013, 429, 142–148) that the contact angle θc of a liquid droplet on any given surface can be controlled by immersing it in an appropriate surrounding environment. Here, we report the first experimental demonstration of such an in situ contact angle tuning of silver (Ag) nanoparticles on quartz substrates via nanosecond pulsed laser heating under various fluid ambients, like air, water, and glycerol. Nanosphere lithography (NSL) was used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…We have built our switching idea based on a newly discovered effect in which the shape of the particle can be changed based on the conditions under when the particle is irradiated. In a recent work by our group [24], we demonstrated that Ag nanoparticles fabricated by laser melting in air, water and glycerol environments yielded significantly different shapes, with the glycerol leading to a near-spherical shape, while air produced near-hemispherical shape particles. This shape difference was attributed to different interfacial energies involved, with the glycerol-substrate and glycerol-Ag interfacial energies being larger than the air-substrate and air-Ag interfacial energy, this leading to higher contact angles for the glycerol case, as predicted by Young's equation [32].…”
Section: Analysis and Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We have built our switching idea based on a newly discovered effect in which the shape of the particle can be changed based on the conditions under when the particle is irradiated. In a recent work by our group [24], we demonstrated that Ag nanoparticles fabricated by laser melting in air, water and glycerol environments yielded significantly different shapes, with the glycerol leading to a near-spherical shape, while air produced near-hemispherical shape particles. This shape difference was attributed to different interfacial energies involved, with the glycerol-substrate and glycerol-Ag interfacial energies being larger than the air-substrate and air-Ag interfacial energy, this leading to higher contact angles for the glycerol case, as predicted by Young's equation [32].…”
Section: Analysis and Discussionmentioning
confidence: 95%
“…The single pulse irradiation was performed at normal incidence by the linearly polarized laser beam of area 1 mm 2 . This technique was developed recently to synthesize nearspherical nanoparticles on quartz substrates via a dewetting process, as reported in reference [24]. The resulting nanostructures were then investigated by high resolution imaging using a ZEISS Merlin scanning electron microscope (SEM) in plan and side view orientations.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation